1983
DOI: 10.1212/wnl.33.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cerebrovascular CO 2 reactivity in stroke‐age normal controls

Abstract: We used the noninvasive 133-xenon inhalation technique to determine cerebral hemodynamics in 55 normal volunteers aged 18 to 88. Values for cerebral blood flow and cerebrovascular CO2 reactivity in fast-clearing tissue (flow gray) and slow-clearing tissue (flow white) were examined as functions of age and in relation to hematocrit, blood pressure, and evidence of extracranial vascular disease. Flow gray declined linearly with age, but no corresponding change was found in flow white or in CO2 reactivity. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 0 publications
9
71
0
2
Order By: Relevance
“…Significantly higher CBF values in female subjects were also reported by Shaw et al (1984) and Gundling et al (1985). Their findings to gether with those of Davis et al (1983), who showed that the mean flow differences were present until the sixth decade, are in good agree ment with our data. Fairly consistent results thus indicate that women have a higher mean CBF level than do men.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significantly higher CBF values in female subjects were also reported by Shaw et al (1984) and Gundling et al (1985). Their findings to gether with those of Davis et al (1983), who showed that the mean flow differences were present until the sixth decade, are in good agree ment with our data. Fairly consistent results thus indicate that women have a higher mean CBF level than do men.…”
Section: Discussionsupporting
confidence: 93%
“…( , 1987a) demonstrated significantly higher mean hemispheric blood flow levels in fe male compared with male subjects. Higher flow levels in women were also reported by Davis et al (1983), Shaw et al (1984), and Gundling et aI. (1985).…”
supporting
confidence: 58%
“…Influence of age on cerebral blood flow and cerebrovascular reactivity at rest and during exercise Older individuals have been reported to have a maintained (Davis et al 1983;Ito et al 2002;Kastrup et al 1998;Schwertfeger et al 2006;Galvin et al 2010) and reduced (Reich and Rusinek 1989;Yamamoto et al 1980) hypercapnic cerebrovascular reactivity compared to younger individuals. The reasons for the discrepancy are likely to be multi-factorial and may include differences in CBF measurement technique (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of healthy ageing on cerebrovascular CO2 reactivity is less clear, however. Hypercapnic reactivity has been found to be both lower (Reich and Rusinek 1989;Yamamoto et al 1980) and unchanged (Davis et al 1983;Ito et al 2002;Kastrup et al 1998;Schwertfeger et al 2006;Galvin et al 2010) with advancing age, while hypocapnic reactivity has been found to be elevated (Galvin et al 2010), unchanged (Ito et al 2002) and reduced (Yamaguchi et al 1979;Tsuda and Hartmann 1989). Differences in measurement technique, stimulus magnitude (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…4,15,17,[31][32][33] Previous studies of aging effects on cerebral CO2 reactivity often were conducted either during hypocapnia or hypercapnia separately. 8,9,20,28,29 Thus, findings of this study can be compared directly with those conducted under similar conditions. 8,9,20,28,29 Second, different from previous studies which have used prolonged rebreathing protocols (B5-7 minutes) to induce a wide range of changes in arterial CO2, a relatively short period of 3 minutes was used in this study to induce a moderate increase in EtCO2 and linear increases in CBFV to facilitate data analysis.…”
Section: Methodological Considerations and Study Limitationsmentioning
confidence: 95%